2020
DOI: 10.7717/peerj.9322
|View full text |Cite
|
Sign up to set email alerts
|

Air transportation, population density and temperature predict the spread of COVID-19 in Brazil

Abstract: There is evidence that COVID-19, the disease caused by the betacoronavirus SARS-CoV-2, is sensitive to environmental conditions. However, such conditions often correlate with demographic and socioeconomic factors at larger spatial extents, which could confound this inference. We evaluated the effect of meteorological conditions (temperature, solar radiation, air humidity and precipitation) on 292 daily records of cumulative number of confirmed COVID-19 cases across the 27 Brazilian capital cities during the 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
3
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 29 publications
5
97
3
7
Order By: Relevance
“…Huang et al described that 60% of all COVID-19 cases are found in places with an air temperature between 5 °C and 15 °C [105]. In Brazil a 1 °C increase in temperature has been associated with a decrease in confirmed cases of 8% [106]. In Wuhan and Xiaogan temperature was the only meteorological parameter constantly but inversely correlated with COVID-19 incidence [107].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Huang et al described that 60% of all COVID-19 cases are found in places with an air temperature between 5 °C and 15 °C [105]. In Brazil a 1 °C increase in temperature has been associated with a decrease in confirmed cases of 8% [106]. In Wuhan and Xiaogan temperature was the only meteorological parameter constantly but inversely correlated with COVID-19 incidence [107].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Furthermore, since the beginning of this outbreak, numerous researches have been going on to understand the factor affecting the transmission of SARC-CoV-2, in particular trying to find the link of host immunity, population density, and climate/environmental conditions (Pequeno et al 2020;Wu et al 2020a, b;Li et al 2020). Air pollution is known to cause numerous respiratory diseases and it is the longer the exposure, the higher is the risk theory (Gorai et al 2016); therefore, there has been considerable interest in understanding whether ambient air pollutants such as PM 2.5 , PM 10 , NO x , and CO are associated with the incidence of the COVID-19 (Zoran et al 2020;Li et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…acute) exposure (measured as the temporal variation of air pollutants), Xu et al (2020) (in 33 locations in China), Zhu et al (2020) (in 120 cities in China), Jiang et al (2020) (3 cities in China), Li H et al (2020) (2 cities in China) and Adhikari et al (2020) (in Queens, New York) found significantly positive associations between the short-term exposure to air pollutants with newly confirmed cases. Furthermore, as Domingo et al (2020) point out, in a very recent review, the results of most of the studies suggest that the long-term exposure to air pollutants might lead to more severe and lethal forms of Most of the studies evaluating socioeconomic and demographic variables (four of the six studies) considered population density (Coccia, 2020;Ahmadi et al, 2020;Pequeno et al, 2020;and You et al 2020). Three studies evaluated the influence of income (Azar et al, 2020;You et al, 2020;and Price-Haywood et al, 2020).…”
mentioning
confidence: 99%